Membrane Morphologies: Heterogeneous Forces and Articulated Material Form. (September 2015) - Ahlquist, Sean; Menges, Achim
<x xml:space="preserve">Abstract</x> Material behaviour is induced at the moment a structure, with its accompanying system of energies, is assembled. The research introduced here by Sean Ahlquist, Assistant Professor at the University of Michigan, in textile manufacturing and membrane structures challenges the concept of assembly in an architectural context, where form emanates not only from the integration of forces and differentiated materials, but also through the pervasive influence of structural action at the moment of fibre construction and composition.